Implementation of Public Policy in Cultural Heritage Preservation: A Case Study of Sunyaragi Cave Management in Cirebon City - Usmara, Gunawan Fadillah; Rohida, Leni (PT FORMOSA CENDEKIA GLOBAL, 2026)
Preserving national identity and supporting culture based sustainable development require safeguarding cultural heritage. One legacy of the Cirebon Sultanate is the Sunyaragi Cave, which holds historical, architectural, and cultural significance. Although preservation regulations exist, challenges remain in policy implementation. This study evaluates the Sunyaragi Cave preservation policy by examining policy actors, implementation mechanisms, and supporting and hindering factors. Using a qualitative case study, data were collected through interviews with the Cirebon City Culture and Tourism Office and the Sunyaragi Water Park Management Agency, along with field observations. Data were analyzed using George C. Edwards III’s implementation model and street level bureaucracy. Findings show that implementation is suboptimal due to weak coordination, limited resources, and insufficient public communication. Inclusive preservation requires collaborative governance.